Composição, distribuição e estrutura das assembleias de peixes nas regiões estuarinas e marinhas costeiras adjacentes impactadas pelo maior desastre ambiental com mineração do Brasil - Oliveira, Rafael Lima (2024)
The growing need to characterize and quantify biodiversity in its multiple dimensions has highlighted the importance of integrating different approaches in studying the relationships of organisms with environmental fluctuations at different spatial and temporal scales. In this context, the present thesis explored different ecological descriptors of fish assemblages and their relationships with local and spatial environmental variables, considering four estuaries and their adjacent coastal marine areas. As the studied estuarine-coastal systems differ considerably in their geomorphological and hydrographic characteristics, we hypothesized that different environmental factors at different scales would influence the ecological descriptors of fish assemblages. In chapter 1, we evaluated the correlation between species richness and density of fish and physicochemical water variables (salinity, temperature, dissolved oxygen, pH, and turbidity) using generalized linear mixed models (GLMMs). The most explanatory models for each response variable (richness and density) included different sets of predictor variables. For species richness, depth and turbidity were included in all the most explanatory models. On the other hand, most environmental variables were retained in the most explanatory models for the response variable density. In chapter 2, we quantified the contribution of sites and species to beta diversity and their relationship with local environmental variables, spatial variables, and fish assemblage metrics. The results indicated that the sites that contributed most to beta diversity variation were the estuarine areas. Variations in site contributions were mainly influenced by salinity, depth, and temperature. In chapter 3, we evaluated the composition and distribution of ecological guilds and their variations across rainy and dry seasons. The general patterns of guild dominance indicated a greater contribution of marine-origin species guilds throughout the systems. Freshwater species guilds contributed more in areas associated with the São Mateus and Doce River estuaries. Throughout the rainy and dry seasons, most of the variability in species abundances was related to losses of individuals, mainly of dominant species. Among the four estuarine-coastal systems evaluated, only Caravelas and Doce River indicated significant seasonal changes, with a dominance of the gain component of individuals in Caravelas and losses of individuals in the Doce River. Finally, in chapter 4, we estimated the length-weight relationship for the species Catathyridium garmani (46 individuals), Pseudauchenipterus affinis (159 individuals), Cathorops arenatus (15 individuals), and Anchoviella brevirostris (83 individuals). All 21 estimates were significant, and new total length values for two species were reported. The results emphasized the influence of local environmental variables on the ecological descriptors of fish assemblages, especially in estuarine areas. On the other hand, the influence of spatial variables also indicates potential sources of environmental variation on broader scales, which can also influence the composition and distribution patterns of the ichthyofauna. Thus, it is important to access estuarine marine gradients at multiple spatial and temporal scales